Health care for women in menopause - O.M. Barna; O.О. Yefimenko; N.V. Kosei; L.A. Mishchenko; N.Y. Pedachenko; T.F. Tatarchuk (Publishing House TRILIST, 2023)
Clinical lecture is intended for general practitioners - family doctors who provide medical assistance to women with menopausal disorders and are based on the Unified clinical protocol of primary, secondary (specialized), tertiary (highly specialized) heath care "Menopausal disorders and other disorders in the perimenopause" approved by the order of the Ministry of Health of Ukraine dated June 17, 2022 No. 1039. Clinical lecture provides methods and algorithms for diagnosis and treatment of associated with menopause disorders, which will allow forming a comprehensive management strategy of women during menopause by a family doctor in Ukraine and will contribute to improving their health and quality of life. Today, there are no reliable signs that predict the severity and duration of menopausal disorders, so women should focus on a healthy lifestyle as a way to prevent severe menopausal disorders. To clarify the stages of reproductive aging, it is advisable to use the Stages of Reproductive Aging Workshop (STRAW+10). All women over 40 who come for a visit should be asked 6 questions to identify menopausal syndrome. The international Menopause Rating Scale is used to determine the severity of menopause symptoms. Women with symptoms of menopause should be referred to an obstetrician-gynecologist. Treatment of patients with menopausal disorders is carried out by a general practitioner - a family doctor and is carried out using non-medicinal methods and pharmacotherapy. The family doctor can prescribe non-hormonal drugs. Hormonal treatment of menopause symptoms is prescribed by an obstetrician-gynecologist. Treatment of accompanying pathology is prescribed by relevant specialists in accordance with current standards of medical care. Patients with perimenopausal and menopausal disorders need to be monitored by a general practitioner - a family doctor, who maintains the medical documentation and helps the patient comply with the recommendations of specialists.